2020
DOI: 10.1038/s41598-020-74223-5
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic oligomerization and self-assembly of structurally diverse xenobiological monomers

Abstract: Prebiotic chemists often study how modern biopolymers, e.g., peptides and nucleic acids, could have originated in the primitive environment, though most contemporary biomonomers don’t spontaneously oligomerize under mild conditions without activation or catalysis. However, life may not have originated using the same monomeric components that it does presently. There may be numerous non-biological (or “xenobiological”) monomer types that were prebiotically abundant and capable of facile oligomerization and self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 82 publications
1
19
0
Order By: Relevance
“…A wide range of scenarios has been proposed, with varying degrees of scope. Most begin with a specific venue for the initiation of prebiotic chemistry, although some advocate for the role of multiple environments in life’s origin [ 7 , 8 , 9 , 10 ]. Proposed beginning venues include marine alkaline hydrothermal vents, either within microchambers [ 11 , 12 , 13 , 14 , 15 , 16 ] or iron (oxy)hydroxide (green rust) mounds [ 2 , 17 ], hydrothermally/volcanically charged sediments [ 18 , 19 ], terrestrial geothermal hot springs [ 20 ] including at their edges [ 21 , 22 ], within the pores of pumice rafts [ 23 , 24 ], between layers of micas [ 25 ], on clay surfaces [ 26 ] or greenalite nanoparticles [ 27 ], and even within the atmosphere as the key venue for initial biosynthesis fueled by a major meteorite impact [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of scenarios has been proposed, with varying degrees of scope. Most begin with a specific venue for the initiation of prebiotic chemistry, although some advocate for the role of multiple environments in life’s origin [ 7 , 8 , 9 , 10 ]. Proposed beginning venues include marine alkaline hydrothermal vents, either within microchambers [ 11 , 12 , 13 , 14 , 15 , 16 ] or iron (oxy)hydroxide (green rust) mounds [ 2 , 17 ], hydrothermally/volcanically charged sediments [ 18 , 19 ], terrestrial geothermal hot springs [ 20 ] including at their edges [ 21 , 22 ], within the pores of pumice rafts [ 23 , 24 ], between layers of micas [ 25 ], on clay surfaces [ 26 ] or greenalite nanoparticles [ 27 ], and even within the atmosphere as the key venue for initial biosynthesis fueled by a major meteorite impact [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we propose an alternative Panspermia hypothesis utilizing materials in the form of polymeric gels that can potentially be an experimental framework to study the Panspermia hypothesis and the OoL. We have briefly shown that polymer gels (in the form of polyesters) formed from a variety of prebiotically available hydroxy acids, [128,144] amino acids and cyclic compounds, [138] showed cell-like functionality and have the potential to lead to the emergence of life via chemical evolution. While these polymeric gels' cell-like functions [127,128,138] provide glimpses of the potential of non-biomoleculebased OoL models (e.g., [137,177,210]), its robustness as a Panspermia seed, especially during spaceflight and also impact shock upon arriving in a recipient planet is unknown, require necessary investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that, around four billion years ago, a creative phase of pre-Darwinian chemical evolution pared down the number of potential building blocks to form oligomers and polymers with levels of functionally required for Darwinian processes [15,[19][20][21][22][23][24]. Numerous models have been proposed to explain various chemical and physical aspects of the origins of biopolymers [15,18,22,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. The chemistry of water and the condensation-dehydration of building blocks into chimeric metabolites, oligomers and polymers are important features of these models.…”
Section: Introductionmentioning
confidence: 99%